2004
DOI: 10.1128/jvi.78.6.2701-2710.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Dependent Immunity Is Essential for Resistance to Primary Dengue Virus Infection in Mice, Whereas T- and B-Cell-Dependent Immunity Are Less Critical

Abstract: Dengue virus (DEN) causes dengue fever and dengue hemorrhagic fever/dengue shock syndrome, which are major public health problems worldwide. The immune factors that control DEN infection or contribute to severe disease are neither well understood nor easy to examine in humans. In this study, we used wild-type and congenic mice lacking various components of the immune system to study the immune mechanisms in the response to DEN infection. Our results demonstrate that alpha/beta interferon (IFN-␣/␤) and IFN-␥ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
281
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(306 citation statements)
references
References 53 publications
15
281
1
5
Order By: Relevance
“…The host type I IFN response is critical for restricting replication and dissemination of flaviviruses 10,[54][55][56][57] and JEV SA14-14-2 is capable of inducing morbidity in IFN-deficient mice, 58 indicating that innate-immune antiviral mechanisms contribute to its attenuated phenotype. Studies in primary human monocyte-derived macrophages showed that JEV SA14-14-2 induced similar levels of type I IFN as WT JEV but is more sensitive to its affects.…”
Section: Discussionmentioning
confidence: 99%
“…The host type I IFN response is critical for restricting replication and dissemination of flaviviruses 10,[54][55][56][57] and JEV SA14-14-2 is capable of inducing morbidity in IFN-deficient mice, 58 indicating that innate-immune antiviral mechanisms contribute to its attenuated phenotype. Studies in primary human monocyte-derived macrophages showed that JEV SA14-14-2 induced similar levels of type I IFN as WT JEV but is more sensitive to its affects.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are challenging, since the mortality rate of DHF is significantly lower than those of other viral hemorrhagic diseases and deaths typically occur late in infection (4). The lack of a relevant animal model that mimics the pattern of plasma leakage in DHF has not allowed an in vivo experiment to precisely delineate the role of VEGF relative to other cytokines reported to be elevated in DHF, such as IL-2, IFN-␥, tumor necrosis factor alpha, and IFNs, in plasma leakage (6,19,41). However, the temporal pattern of VEGF and its known biological effects argue for its role as a mediator involved in plasma leakage in DHF.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that during DENV infection, iNKT cells produce IFN-␥ and that iNKT cells trans-activate NK cells to produce it. Considering the critical function of IFN-␥ in restricting DENV replication, 48,85 the lack of function of the iNKT cell/NK cell pathway in virus containment in this system is somewhat surprising. The role of NK cells during DENV infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…with 30 LD 50 DENV, a lethal dose that caused death of all animals between days 6 and 8. One LD 50 corresponds to the inoculum necessary to kill 50% of 4-week-old BALB/c mice, a more susceptible strain, 48 and corresponds to approximately 20 PFUs. Clinical manifestations, in particular hypernociception, were observed at about day 3.…”
Section: Infection and Assessment Of Diseasementioning
confidence: 99%
See 1 more Smart Citation